The Role of the Tahfidzul Qur’an Program in Shaping Students’ Discipline and Independence: An Adab al-‘Alim wa al-Muta’allim Perspective - Egara Dinnul Iza; Asriana Kibtiyah; Khoirotul Idawati; Rofiatul Hosna (Journal of Contemporary Islamic Education, 2026)
Character education should not merely emphasize intellectual development but also the internalization of moral and ethical values to cultivate responsible and integrity-driven individuals. However, current educational practices still tend to prioritize cognitive achievement, resulting in an imbalance between academic performance and students’ affective-moral development. This study aims to examine the role of the Tahfidzul Qur’an program in fostering students’ discipline and independence at MA Unggulan Rohmatul Ummah Mojokerto, grounded in the perspective of Adab al-‘Alim wa al-Muta’allim. This research employs a qualitative descriptive approach with a case study design. Data were collected through interviews, observations, and documentation involving teachers, the principal, and students. The findings reveal that the Tahfidzul Qur’an program plays a significant role in cultivating students’ discipline through structured memorization schedules, while also encouraging their independence in managing learning responsibilities. Furthermore, the integration of ethical values derived from Adab al-‘Alim wa al-Muta’allim—such as discipline, humility, and respect for knowledge—substantially strengthens students’ character formation. This study contributes to the field of Islamic education by offering an empirical model of character development through Qur’anic memorization programs integrated with ethical teachings. In conclusion, these findings underscore the strategic importance of the Tahfidzul Qur’an program in nurturing disciplined and independent students, as well as its relevance for broader implementation in contemporary Islamic education.